PENGARUH CONTENT MARKETING DAN LIVE STREAMING TERHADAP IMPULSIVE BUYING PRODUK FASHION DENGAN MEDIASI BRAND AMBASSADOR MELALUI APLIKASI TIKTOK PADA GENERASI Z - Anggraini, Melani Putri; Hadita, Hadita; Winarso, Widi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to analyze the influence of content marketing and live streaming on impulsive buying of products with brand ambassador mediation through the TikTok application on generation z. The research method used is the purposive sampling method by distributing questionnaires via gform to respondents. The data analysis technique in this study used Structural Equation Modeling Partial Least Square (SEM-PLS) analysis with the help of SmartPLS software version 4.1.0.9. The results of the study showed that content marketing and live streaming had a significant effect on impulsive buying, brand ambassadors had a significant effect on impulsive buying, and that content marketing and live streaming through brand ambassadors had a significant effect on impulsive buying.